Risk factors of chronic renal disease in patients from the II Frente municipality - Gertrudis Torres Rondón; Yoandri Bandera Ramos; Pablo Yulior Ge Martínez; Irlán Amaro Guerra (Centro Provincial de Información de Ciencias Médicas, 2017)
An observational analytic case-control study, that included 65 patients (cases) was carried out. They were assisted in the Nephrology Service due to chronic renal disease and 130 supposedly healthy patients (controls), from January to December, 2014, aimed at determining some risk factors associated to the emergence of this disease in the doctor´s offfices of the urban area in II Frente. Sex, the family pathological history,   hypertension, diabetes mellitus and nicotine addiction were related to the emergence of the chronic renal disease. The attributable risk in exposed percentage was also determined to identify those predisposing factors that when acting on them, a higher impact would be achieved in the exposed population, that is: hypertension, diabetes mellitus and nicotine addiction.